2022
DOI: 10.1186/s13059-022-02615-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell isoform analysis in human immune cells

Abstract: High-throughput single-cell analysis today is facilitated by protocols like the 10X Genomics platform or Drop-Seq which generate cDNA pools in which the origin of a transcript is encoded at its 5′ or 3′ end. Here, we used R2C2 to sequence and demultiplex 12 million full-length cDNA molecules generated by the 10X Genomics platform from ~3000 peripheral blood mononuclear cells. We use these reads, independent from Illumina data, to identify B cell, T cell, and monocyte clusters and generate isoform-level transcr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 71 publications
(85 reference statements)
3
30
0
Order By: Relevance
“…This simple and universal protocol is a major advantage over all targeted sequencing techniques (Sanger, Illumina, PacBio/ONT; 9, 10, 17, 20 ). It is also much simpler, cheaper and less prone to chimerism than whole-transcriptome concatemer nanopore sequencing 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This simple and universal protocol is a major advantage over all targeted sequencing techniques (Sanger, Illumina, PacBio/ONT; 9, 10, 17, 20 ). It is also much simpler, cheaper and less prone to chimerism than whole-transcriptome concatemer nanopore sequencing 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Lowden and Henry 20 found that, without error correction steps, 75-80% of antibody fragment reads were unable to have their CDR3 identified. Error correction methods that rely on the sequencing of concatemers from rolling circle amplification can successfully reconstruct BCR sequences from single B cells 22 , however they require more time and computational power than NAb-seq. Similarly, the assembly-based approach employed to characterize cancerous B cells 21 , though effective, is slower and more computationally intensive than the simple consensus strategy implemented by NAb-seq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential isoform expression between cell types and across conditions plays a major role in the diversification of the proteome ( Nilsen and Graveley, 2010 ) and functionality of transcripts in the cell ( Yang et al , 2016 ). Long-read sequencing has become widely used to address this problem ( Au et al , 2013 ; Bolisetty et al , 2015 ; Koren et al , 2012 ; Leung et al , 2021 ; Oikonomopoulos et al , 2016 ; Ruiz-Reche et al , 2019 ; Schulz et al , 2021 ; Sharon et al , 2013 ; Tilgner et al , 2015 ), and with applications to single-cell isoform sequencing studies ( Arzalluz-Luque et al , 2022 ; Gupta et al , 2018 ; Hardwick et al , 2022 ; Joglekar et al , 2021 ; Volden and Vollmers, 2022 ). These approaches have been reviewed in Hardwick et al (2019) .…”
Section: Introductionmentioning
confidence: 99%
“…Differential isoform expression between cell types and across conditions plays a major role in the diversification of the proteome (1) and functionality of transcripts in the cell (2). Long-read sequencing has become widely used to address this problem (3)(4)(5)(6)(7)(8)(9)(10)(11), and with applications to single-cell isoform sequencing studies (12)(13)(14)(15)(16). These approaches have been reviewed in Hardwick et al, 2019 (17).…”
Section: Introductionmentioning
confidence: 99%